Pharmacology of modern ACE inhibitors: moexipril example - D. P. Khloponin; Yu. N. Krotova; I. V. Ivanov (Кардиоваскулярная терапия и профилактика, 2007)
ACE inhibitors are widely used in the treatment of arterial hypertension, chronic heart failure, and other cardiovascular pathology. The article is devoted to ACE pharmacology and their optimal use in clinical practice.